La isla del tesoro/Tresaure Island - Robert Louis Stevenson (Robert Louis Stevenson, 2014)
"Una mañana, un viejo marinero que tenía la cara marcada con la cicatriz de un sable, llegó hasta nuestra casa arrastrando un gastado baúl. Era alto y fuerte y llevaba el pelo recogido en una trenza negra. Sus manos, con las uñas sucias y recomidas sujetaban un bastón. Dentro de la posada, el viejo marinero pidió un vaso de ron y, apurándolo de un solo trago, comenzó a hablar con mi madre."El joven Jim Hawkins, hijo de la mesonera de un pequeño pueblo de la costa de Inglaterra, conoce a un viejo marinero borracho y malhumorado, que al morir deja el mapa de un tesoro: un codiciado alijo de oro y plata enterrado por el legendario pirata Flint en una lejana isla tropical.Jim consigue abordar un barco para ir a la isla, pero, mezclada con la tripulación, una banda de piratas capitaneados por John Silver también perseguirá el botín. Empieza la aventura. Treasure Island is an adventure novel by Scottish author Robert Louis Stevenson, narrating a tale of "buccaneers and buried gold". First published as a book on 23 May 1883, it was originally serialized in the children's magazine Young Folks between 1881 and 1882 under the title Treasure Island or, the mutiny of the Hispaniola with Stevenson adopting the pseudonym Captain George North. Traditionally considered a coming-of-age story, Treasure Island is a tale known for its atmosphere, characters and action, and also as a wry commentary on the ambiguity of morality - as seen in Long John Silver - unusual for children's literature every now and again. It is one of the most frequently dramatized of all novels. The influence of Treasure Island on popular perceptions of pirates is enormous, including treasure maps marked with an "X", schooners, the Black Spot, tropical islands, and one-legged seamen carrying parrots on their shoulders.